Open data intermediaries: coproduction in budget transparency. Issue 1 (20th March 2017) - da Silva Craveiro, Gisele; Albano, Claudio
Abstract : Purpose: Although more public sector information is disclosed in an open format, the intermediaries are the key element to have value creation from it. This study aimed to identify elements about the role of these stakeholders: their characteristics, resources and partnerships within an ecosystem of budget transparency and open government data, in particular, to identify initiatives and opportunities that enable the co-production of value from public sector information. Design/methodology/approach: The study was conducted in four Latin American countries, and data collection was carried out through interviews and document analysis. Findings: The paper identifies intermediaries' profiles, their network, results achieved and lessons learned. Originality/value: This is the first study to cover in depth the intermediaries in a regional budget transparency ecosystem. Some findings emphasize the intermediary's role, and others offered the authors elements to propose a framework for citizen coproduction that extends citizen sourcing and government as platform models, as some co-production initiatives identified seem to extrapolate their limits definitions.